Cloudy band observations for annual layer counting on the GRIP and NGRIP, Greenland, deep ice core samples (scientific note) - Shimohara, Kimiko; Miyamoto, Atsushi; Hyakutake, Kinji; Shoji, Hitoshi; Takata, Morimasa; Kipfstuhl, Sepp (2003)
P(論文) Cloudy band stratigraphy was observed in the GRIP and NGRIP, Greenland ice cores. Gray value profiles obtained from the photographic recording were analyzed to extract annual layer signals. Simple counting of gray value peaks is effective enough when annual layer thickness is relatively small (smaller than approximately 20 mm), but smoothing of the gray value profile is needed when annual layer thickness is larger. Smoothing can be done by adopting a running mean over a range of half of annual layer thickness estimated from ice flow modeling. A comparison of the DEP profile with the gray value profile revealed that the DEP profile seems to reflect the seasonal variation in general, but not exactly. departmental bulletin paper